Green Tea Consumption and Esophageal Cancer Risk: A Meta-analysis. (2nd April 2020) - Yi, Yu; Liang, Hailong; Jing, Huang; Jian, Zhang; Guang, Yang; Jun, Zhang; Zhu, Hongfa; Jian, Li
Abstract: Background: The protective role of green tea against cancer is still unknown. Objectives: To investigate the association between green tea consumption and esophageal cancer risk through meta-analysis. Methods: We searched MEDLINE, EMBASE, Web of Science and Cochrane Library for studies on the relationship between green tea and esophageal cancer risk. We assessed heterogeneity ( I 2 ) and publication bias (Begg's and Egger's tests). Pooled relative risks (RRs) or odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using random effects models. Results: A total of 20 studies were included. The RRs for all studies was 0.65 (95% CI: 0.57–0.73), with I 2 = 75.3% and P  = 0. In the subgroup analysis, the following variables showed marked heterogeneity: Asian (RR: 0.64; 95% CI: 0.56–0.73) and non-Asian countries (RR: 0.74; 95% CI: 0.45–1.03), female (RR: 0.55; 95% CI: 0.39–0.71) and male + female (RR: 0.64; 95% CI: 0.54–0.75), case–control study (RR: 0.62; 95% CI: 0.52–0.71), impact factor >3 (RR: 0.65; 95% CI: 0.56–0.75), impact factor <3 (RR: 0.64; 95% CI: 0.48–0.80), Newcastle–Ottawa Scale >7 (RR: 0.82; 95% CI: 0.66–0.97) and Newcastle–Ottawa Scale ≤7 (RR: 0.59; 95% CI: 0.49–0.68). Conclusion: Green tea consumption could be a protective factor for esophageal cancer.